Factors associated with the use of non-pharmacological analgesia for labor pain management. (13th November 2019) - Merrer, J; Chantry, A A; Khoshnood, B; Blondel, B; Le Ray, C; Bonnet, M P
Abstract: Background: For a decade, pain labor management has evolved: if neuraxial analgesia remains the gold standard, non-pharmacological methods are developing. We aimed to identify individual and organizational factors associated with the use of non-pharmacological analgesia, combined or not with neuraxial analgesia. Methods: Women who attempted vaginal delivery with labor analgesia were selected from the 13, 147 participants of the 2016 National Perinatal Survey. Labor analgesia was studied as follows: neuraxial analgesia only (NA), non-pharmacological analgesia only (NPA) or neuraxial and non-pharmacological methods combined (NA+NPA). Associations between individual and organizational characteristics were studied using a multilevel multinomial logistic regression. Results: Among the 9 231 women included, 62.4% had NA only, 6.5% had NPA only and 31.1% had NA+NPA. Both NPA and NA+NPA were associated with multiparity with antenatal classes, educational level ≥ 5 years post graduate, antenatal preference to deliver without NA, and delivery in public maternity units. The use of NPA only was positively associated with non-permanent availability of the anesthesiologist and with a high number of midwives per shift in maternity units. Contrastingly, NPA only was negatively associated with foreign nationality and oxytocin use for induction or augmentation of obstetrical labor. NA+NPA was positively associated with primiparity with antenatal classes, but negatively with inadequate prenatal care. Conclusions: Less than 40% of parturients used non-pharmacological analgesia during labor and for the most of them as complementary methods to neuraxial analgesia. NPA and NA+NPA were associated with individual characteristics as well as characteristics of management of labor and organization of maternity units. Non-pharmacological analgesia appears to be dedicated to high educated and well-integrated women in perinatal health care system. Key messages: Less than 40% of parturients used non-pharmacological analgesia during labor and for the most of them as complementary methods to neuraxial analgesia. Non-pharmacological analgesia appears to be dedicated to high educated and well-integrated women in perinatal health care system.